Electrochemical Study of Carbon Nanotubes/Nanohybrids for Determination of Metal Species Cu2+ and Pb2+ in Water Samples - Andréa Claudia Oliveira Silva; Luis Carlos Ferreira de Oliveira; Angladis Vieira Delfino; Mario Roberto Meneghetti; Fabiane Caxico de Abreu (Journal of Analytical Methods in Chemistry)
The use of nanomaterials, such as nanoparticles and nanotubes, for electrochemical detection of metal species has been investigated as a way of modifying electrodes by electrochemical stripping analysis. The present study develops a new methodology based on a comparative study of nanoparticles and nanotubes with differential pulse anodic stripping voltammetry (DPASV) and examines the simultaneous determination of copper and lead. The glassy carbon electrode modified by gold nanoparticles demonstrated increased sensitivity and decreased detection limits, among other improvements in analytical performance data. Under optimized conditions (deposition potential −0.8 V versus Ag/AgCl; deposition time, 300 s; resting time, 10 s; pulse amplitude, 50 mV; and voltage step height, 4 mV), the detection limits were 0.2279 and 0.3321 ppb, respectively, for determination of Pb2+ and Cu2+. The effects of cations and anions on the simultaneous determination of metal ions do not exhibit significant interference, thereby demonstrating the selectivity of the electrode for simultaneous determination of Pb2+ and Cu2+. The same method was also used to determine Cu2+ in water samples.